Integration of Green Accounting Into Romanian Accounting System - Mihaela Ungureanu (CES Working Papers, 2012)
The aim of this paper is to present the concept of green accounting, its emergence at an international level, its entry in the Romanian economic environment and, especially, the way it is understood and applied in Romania. It seeks the awareness of managers and accounting professionals on this issue, especially in the context of growing pressure for environmental protection, from the general public, media and investors. An essential role is held by the accounting profession and its relevant legislation, through the elaboration of standards and guidelines in order to support the efforts of changing the mentality of business environment. The companies are also concerned for the future and not only for the present and they understand that environmental investments are not unnecessary expenses that burden the activities, but long-term profits prerequisites. Understanding the concept is difficult without an agreement on its definition. Specialized literature presents different definitions, each author with his own interpretation and vision. This is why professional accountants' reluctance to adopt new ideas and practices of green accounting, this being an unknown territory to them and difficult to entered.
Keywords: M41; Q51; Q56; 330; green accounting; environmental costs; indicators; benefits; performance Romania